PENGEMBANGAN BAHAN AJAR BERBASIS FLIPBOOK DIGITAL PADA MUATAN ILMU PENGETAHUAN ALAM UNTUK MENINGKATKAN KOMPETENSI GENERASI ALPHA (STUDI KASUS PESERTA DIDIK LKP HARMONI ALFIANSYAH KABUPATEN BANDUNG) - Risma Sri Rahayu; Kirana Lesmi; Rd. Kiki Abdul Muluk; Iim Khotimah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The emergence of digital technology on a large scale has opened new perspectives for educators to develop variations in their teaching. This study aims to identify obstacles and efforts in improving competency, the process, and implementation of digital flipbook-based development in natural science content to enhance the competency of Generation Alpha. This research is motivated by students' learning needs and the availability of digital technology. The development of teaching materials was designed using Canva Pro and Quiziz, as well as educational games supported by a platform called Wordwall, which creates concrete learning. The method used in this study was Research and Development. The results of the digital flipbook product development showed that the media was declared valid with a